Persepsi Masyarakat Tentang Proses Pencalonan Kepala Pemerintahan Negeri Seith Kecamatan Leihitu Kabupaten Maluku Tengah - Maya Lisa Haupea; A. Bahasoan; Pieter S. Soselisa (Universitas 17 Agustus 1945, 2023)
This research is a descriptive qualitative research. Aims to describe and explain the Public Perception of the Nomination Process of the Head of the Seith Village Government, Leihitu District, Central Maluku Regency. The informants of this research amounted to 10 people. The data needed in this study were collected through observation, interview, and documentation techniques. The data was successfully collected, processed and analyzed with the help of descriptive qualitative analysis techniques. The results of this study show that most of the Seith village community has high support for the nomination process for the head of the Seith village government, but there is not yet a full understanding. This was influenced by supporting factors, namely, the participation of the majority of the community and approval of the nomination of the king based on lineage, despite not having an education equivalent to high school. The process of determining the mata rumah parentah by saniri involves community representatives or community leaders who receive a delegation from saniri, and they agree that there is only one mata rumah parentah to become king, namely the mata rumah parentah Nukuhehe. While the obstacles are, Some people who do not understand the rules governing the process of nominating or appointing the head of government / king, lack of awareness and evaluation, Some people do not agree that the king is based on descent and the influence of the community on issues of interest.